The Balance of HCO3- Secretion vs. Reabsorption in the Endometrial Epithelium Regulates Uterine Fluid pH - Xie, Zhang-Dong; Guo, Yi-Min; Ren, Mei-Juan; Yang, Jichun; Wang, Shao-Fang; Xu, Tong-Hui; Chen, Li-Ming; Liu, Ying (Frontiers in Physiology, 2018)
Uterine fluid contains a high concentration of HCO3– which plays an essential role in sperm capacitation and fertilization. In addition, the HCO3– concentration in uterine fluid changes periodically during the estrous cycle. It is well known that the endometrial epithelium contains machineries involving the apical SLC26 family anion exchangers for secreting HCO3– into the uterine fluid. In the present study, we find for the first time that the electroneutral Na+/HCO3– cotransporter NBCn1 is expressed at the apical membrane of the endometrial epithelium. The protein abundance of the apical NBCn1 and that of the apical SLC26A4 and SLC26A6 are reciprocally regulated during the estrous cycle in the uterus. NBCn1 is most abundant at diestrus, whereas SLC26A4/A6 are most abundant at proestrus/estrus. In the ovariectomized mice, the expression of uterine NBCn1 is inhibited by β-estradiol, but stimulated by progesterone, whereas that of uterine SLC26A4/A6 is stimulated by β-estradiol. In vivo perfusion studies show that the endometrial epithelium is capable of both secreting and reabsorbing HCO3–. Moreover, the activity for HCO3– secretion by the endometrial epithelium is significantly higher at estrus than it is at diestrus. The opposite is true for HCO3– reabsorption. We conclude that the endometrial epithelium simultaneously contains the activity for HCO3– secretion involving the apical SLC26A4/A6 and the activity for HCO3– reabsorption involving the apical NBCn1, and that the acid-base homeostasis in the uterine fluid is regulated by the finely-tuned balance of the two activities.